2012
DOI: 10.1177/0022034512459655
|View full text |Cite
|
Sign up to set email alerts
|

Periostin is Down-regulated during Periodontal Inflammation

Abstract: Periostin, a matricellular adapter protein highly expressed by periodontal ligament fibroblasts, is implicated in the maintenance of periodontal integrity, which is compromised during periodontal diseases. The aim of this study was to explore the influence of chronic periodontal inflammation on tissue periostin levels. Periodontal breakdown was induced in a pre-clinical ligature periodontal inflammatory disease model. Periodontal tissue specimens were harvested at baseline, 2 weeks, and 4 weeks and prepared fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
40
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 25 publications
6
40
0
Order By: Relevance
“…Periodontal tissues in rats were harvested at baseline, 2 and 4 wk after experimental periodontitis induction. Similar to our biochemical findings, periostin levels proportionally decreased over time in response to the inflammatory process . It was also reported that alveolar bone loss inversely correlated with the levels of periostin.…”
Section: Discussionsupporting
confidence: 91%
“…Periodontal tissues in rats were harvested at baseline, 2 and 4 wk after experimental periodontitis induction. Similar to our biochemical findings, periostin levels proportionally decreased over time in response to the inflammatory process . It was also reported that alveolar bone loss inversely correlated with the levels of periostin.…”
Section: Discussionsupporting
confidence: 91%
“…Using an observational prospective case-control study Padial-Molina and colleagues assessed Postn expression in patients with and without periodontitis. Histologically, they identified that Postn protein levels were reduced in the sub-epithelial tissues in patients with periodontitis, which has been shown previously in a rat model to result from inflammatory processes (Padial-Molina, et al, 2012). Following surgery in humans however, Postn levels increased in gingival crevicular fluid (GCF) in both healthy and disease patients, although was higher in the latter group.…”
Section: Periodontiumsupporting
confidence: 67%
“…A ligature‐induced periodontitis model in rats demonstrated the downregulation of POSTN in sites with chronic periodontal inflammation. Lowered levels of POSTN in the inflamed tissue could have resulted in decreased periodontal ligament integrity and subsequent breakdown of the supporting periodontal structures . The findings of downregulated POSTN expression in sites with disease progression are supported by another study, which demonstrated low POSTN levels in patients with chronic periodontitis.…”
Section: Discussionmentioning
confidence: 68%